NEW FINDINGS IN THE SCIENTIFIC HERITAGE OF BURHAN AD-DIN AL-MARGHINANI - Adil Kariev , Hamidulla Aminov (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article is devoted to the issue of inheritance, which is one of the most important and sensitive areas among the Islamic sciences. This legal norm of inheritance in Islam has been resolved with the utmost care, with the aim of ensuring the rights of the heirs as fully as possible. This is a topic that has always been a topical issue in everyday life and is still relevant to Muslims, and it has been the focus of many scholars for centuries. Therefore, the article pays special attention to the works written in this field and their authors, focusing on the historiography of the subject. The importance and relevance of the scientific problem raised in the article is that for many years the work of Burhan ad-Din al-Marghinani on heritage was considered to have not reached us. This article is important in that it focuses on the discovery and scientific circulation of a medieval treatise on Islamic law that was first published in the field of source studies.